The Status of Geometry and Matter in the Reinterpreted WdW Equation - Avadhut V. Purohit (Physical Sciences Forum, 2023)
This paper shows that the field defined by the Wheeler–DeWitt equation for pure gravity is neither a standard gravitational field nor the field representing a particular universe. The theory offers a unified description of geometry and matter, with geometry being fundamental. The quantum theory possesses gravitational decoherence when the signature of <semantics>R(3)</semantics> changes. The quantum theory resolves singularities dynamically. Application to the FLRW <semantics>κ=0</semantics> shows the creation of local geometries during quantum evolution. The 3-metric is modified near the classical singularity in the case of the Schwarzschild geometry.